Pengaruh Kualitas Pelayanan, Kepercayaan Pelanggan dan Kepuasan Pelanggan Terhadap Loyalitas Pelanggan Pada E-Commerce - Arya Daffa Wibisono; Lukman Cahyadi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The rapid development of e-commerce in Indonesia has prompted attention to factors that can maintain business sustainability, especially in terms of customer loyalty. The literature study identified several determining factors, including service quality, customer satisfaction, and brand trust. This research was conducted with the aim of examining the impact of service quality, customer satisfaction, and customer trust on customer loyalty in the Shopee mobile application in Jabodetabek. Using a purposive sampling method, the survey was carried out by distributing questionnaires directly to 120 customers. The results of regression analysis using SPSS refer to a statistical research process where data about the relationship between one or more independent variables (predictors) and one dependent variable (result) is analyzed. SPSS is used as a tool to analyze data and produce regression results. Thus, this research provides important implications that e- commerce mobile applications need to ensure service quality, satisfaction and customer trust to maintain and increase customer loyalty, as well as compete effectively in the online market.